تأثير طريقة تقديم القصة لنتيجة مادة المحادثة لطلاب الصف الثامن المدرسة الثانوية السلفية الشافعية تبوئرنج جومبانج - Zuhro, Fatimah; Qodir, Abdul (Bilingua, 2023)
Learning a foreign language is not easy and requires a long process. Because learning a foreign language is difficult, it is necessary to apply various methods in learning so that learning Arabic can run effectively and conducively. One of the interesting ways among several methods used in language learning is Taqdimul qishah or in English it is called Telling Story. Taqdimul qishah is telling stories using Arabic. The taqdimul qishoh method is a way of conveying or presenting learning material orally in the form of stories or fairy tales from teacher to student or from student to student. This study used a quantitative method (ex post facto) by using a questionnaire for class VIII students with forty-seven students. The distribution of this questionnaire aims to determine whether there is an effect of using this method or not. In determining the learning outcomes of conversation subjects, researchers used the results of oral tests with students arranged by grades. From the results of these scores it was concluded that the scores for the Arabic language subject (conversation subject) were obtained from 47 grade VIII students of MTs Salafiyah Syafi'iyyah Tebuireng Jombang, all of whom met the KKM, with an average score of 88. After distributing the questionnaire and student scores, followed by a partial test of the story presentation method variable (X) with a significance value of 0.004 <0.05, Ho was rejected and Ha was accepted, meaning that the story presentation method variable had a significant effect on the material learning outcomes variable.